Параметрические отказы конденсаторов СМА-166/3-14 в Юго-Западной электроэнергосистеме Украины - Лабзун, М. П.; Лежнюк, П. Д.; Рубаненко, А. Е.; Рудаков, Валерий Васильевич (НТУ "ХПИ", 2014)
Приведены результаты исследования и причин ухудшения изоляционных свойств и показателей надежности высоковольтных конденсаторов связи СМА–166/√3–14 УХЛ1.

The results of research and reasons of worsening of isolating properties and indexes of reliability of high-voltage capacitors of connection SMA–166/√3–14 UHL1 are brought.
Self-reactance refuses of capacitors of СМА-166/3-14 in the South-West elektropower system of Ukraine
Keywords: связь; надежность; изоляция полипропиленовая; масло конденсаторное; high-voltage capacitor; connection; reliability indexes; polipropilen isolation; transformer oil